PENGARUH STRUKTUR MODAL DAN PROFITABILITAS TERHADAP HARGA SAHAM - RICO LINANDA; WINDA AFRIYENIS (Universitas Islam Negeri Imam Bonjol Padang, 2018)
The research theme is: capital market in Indonesia. The research aims to analyze the influence of Debt to Assets Ratio and Return On Asset to stock price. The research variables are: 1) Debt to Assets Ratio, 2) Return On Asset, 3) Stock Price. The results showed the value of Coefficient Determination is equal to 0.106, this shows that the percentage of influence of variable Debt to Assets Ratio and Return On Asset to stock price is equal to 10.6%. Debt to Assets Ratio has no significant effect on stock price. Return On Asset has no significant effect on stock prices. Based on F-Test, Debt to Assets Ratio and Return On Asset did not significantly influence stock price.